The Effect of Perceived Usefulness and Perceived Ease of Use on the Technology Acceptance Model to Use Online Travel Agency - Adi Wicaksono; Anita Maharani (Journal of Business and Management Review, 2020)
Perceived Usefulness (PU) and Perceived Ease of Use (PEU) are factors that can affecting Behavioural Intention (BI) in the Technology Acceptance Model (TAM). This study aims to determine the effect of PU and PEU on BI of PT XYZ users. This research is a non-experimental study using quantitative methods and a random sampling technique. Data were collected through a questionnaire and processed using Statistical Product and Service Solution (SPSS) with a version of 22.00. There were 80 participants in the research, divided into 58 participants who were PT XYZ users and 22 other participants who had never used PT XYZ. The results showed that there was a significant effect of PU and PEU on BI with a value of F = 95.483, R2 = 0.713, and p = 0.000 < 0.05. The contribution of PU and PEU to PEU was 71.3%. Then, partially PU contributed 62.4% and PEU contributed 68.9% to BI. Thus, it can be concluded that for PT XYZ users, the effect of PEU is greater than PU.